Toxicity and genotoxicity in astyanax bimaculatus (Characidae) induced by microcystins from a bloom of microcystis spp - Silva, Ricardo Rocha Pavan da (2010)
Studies of genotoxicity in fish caused by cyanobacterial microcystins can be useful both in determining the sensitivity of native species, as well as comparing exposure routes. The genotoxicity caused by the microcystins LR and LA from a bloom collected in a eutrophic lake, was revealed in the fish Astyanax bimaculatus, a native species from South America. LC50 (72 h) was determined as 242.81 µg L-1 and LD50 (72 h) as 49.19 µg kg-1 bw. There was a significant increase of DNA damage in peripheral erythrocytes, following intraperitoneal injection (ip) with tested concentrations of 24.58 µg kg-1 bw and 36.88 µg kg-1 bw, as well as through body exposure to a concentration of 103.72 µg L-1. Micronucleus (MN) induction was observed after ip injections of 24.58 µg kg-1 bw and 36.88 µg kg-1 bw for 72 h, as well as following body exposure for 72 at 103.72 µg L-1. Thus, both exposure routes resulted in MN induction and DNA damage. Apoptosis-necrosis testing was carried out only by ip injection with concentrations of 24.58 µg -1 bw and 36.88 µg kg-1 bw. Exposure to microcystins at lower concentrations induced more apoptosis than necrosis in peripheral erythrocytes, whereas exposure at higher concentrations gave rise to both conditions. Thus, Astyanax bimaculatus can be considered as a species sensitive to the genotoxic effects caused by microcystins.